Learning Model Innovation: A Study of the Use of Computer Supported Collaborative Learning Models in the Context of Higher Education - Anastya Nida Alhana; Moch. Farich Alfani (Penerbit Hellow Pustaka, 2025)
One learning approach considered capable of increasing learning motivation in higher education is the Computer Supported Collaborative Learning (CSCL) paradigm. To improve learning efficiency, CSCL still requires innovation. The purpose of this study is to assess the implementation and efficacy of the CSCL learning model in higher education. A descriptive approach is the research methodology used, and secondary data are collected from the literature. The use of the CSCL learning model in higher education institutions will be discussed in this study, along with its definition, collaborative learning models, advantages, and impact on learning outcomes. The research findings indicate that because the Computer Supported Collaborative Learning model encourages a more dynamic learning environment in the classroom, this model is considered more beneficial for students than traditional methods. Students can also collaborate more with their peers, which will increase the effectiveness of the learning process.